2012
DOI: 10.31357/jtfe.v2i1.32
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Macroinvertebrate - based Index of Biotic Integrity (M-IBI) for Colombo-Sri Jayawardhanapura Canal System (A new approach to assess stream/ wetland health)

Abstract: Macroinvertebrates have been identified as excellent indicators of stream/ wetland health as they respond rapidly to environmental changes and provide short to medium term pollution history records. Current study was aimed to develop a Macroinvertebrate-based Index of Biotic Integrity (M-IBI) which is a new approach to monitor stream/wetland health of Colombo-Sri Jayewardenepura canal system. Sixty eight macroinvertebrate samples were obtained using a D-framed kick net from ten stations namely Kotte, Nawala, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, absence of a specified, concrete interpretation also means the constructed image of the nation is fuzzy. As the embedded national identity is vague, the symbol can accommodate competing interpretations from groups with conflicting agendas (Perera, 2005). For instance, the British flag has been used to "connote imperial power, tradition and national pride" by the far-right groups; but it was also adopted by the antiauthoritarian mobs to convey "progressive modishness" in the 1960s (Edensor, 2016, 25-26).…”
Section: Collective Memory: a Source Of The Meaningmentioning
confidence: 99%
“…However, absence of a specified, concrete interpretation also means the constructed image of the nation is fuzzy. As the embedded national identity is vague, the symbol can accommodate competing interpretations from groups with conflicting agendas (Perera, 2005). For instance, the British flag has been used to "connote imperial power, tradition and national pride" by the far-right groups; but it was also adopted by the antiauthoritarian mobs to convey "progressive modishness" in the 1960s (Edensor, 2016, 25-26).…”
Section: Collective Memory: a Source Of The Meaningmentioning
confidence: 99%
“…Studies on the relationships between biotic indices and water quality parameters are not common in the inland waters of Sri Lanka. In a study conducted in the Colombo-Sri Jayewardenepura Canal System, 'Reference' and 'Degraded' sampling sites have been identified based on the environmental conditions and macroinvertebrates and a Macroinvertebrate-based Index of Biotic Integrity (M-IBI) has been developed to monitor stream/wetland health (Perera et al 2012). In this study, H', EPT, FBI and TR have been found to be significantly correlated with water quality parameters such as dissolved oxygen concentration, Cl -concentration, total dissolved solids and conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, diversity indices of benthic macro invertebrate communities have been used in several studies in order to monitor the environmental conditions (Gamlath and Wijeyaratne 1997;Dahanayaka and Wijeyaratne 2006;Perera et al 2012;Idroos and Manage 2012;Madhushanka et al 2014). In addition, many studies have concentrated on assessment of physicochemical parameters in the aquatic systems of Sri Lanka in order to identify the source and sink areas of pollutants (Sangakkara and Wijeyaratne 2015;Wijeyaratne 2016).…”
mentioning
confidence: 99%